Some New Results on Antimagic Labeling - Barasara, C. M.; Prajapati, P. J. (Communications in Mathematics and Applications, 2024)
A graph with \(q\) edges is called antimagic if its edges can be labeled with \(1, 2, 3,…, q\) without repetition such that the sums of the labels of the edges incident to each vertex are distinct. In this paper, we study antimagic labeling of one point union of cycle, book graph, path union of \(m\) copies of cycles, \(m\)-splitting of path and \(m\)-splitting of cycle.